Histological and Histochemical Study of Human Glans Penis - Huaraz Loyola, Frida (1999)
OBJECTIVE: To make a contribution to the knowledge about the histological and histochemical features of human glans penis. MATERIAL AND METHODS: We evaluated 12 specimens of glans penis obtained from human cadavers. Specimens were stained with Hematoxy-lin-Eosin, Mallory-Azan trichromic and Masson trichromic for distinguishing morphologic features; argentic staining for neural endings and fibers visualization; periodic acid of Schift for glucoprotein identification and aldehyde-fuchsin for elastic fibers identification. RESULTS: Glans penis exhibited a modified skin with slightly keratinized stratified squamous epithelium. In order to improve the study, glans were divided into three histological areas: distal, middle, and proximal. CONCLUSIONS: We have found some differences between glans tissue as well as the spongy and cavernous bodies penis tissue.